The system in operation. Frontline news - Monika Bogdanowska (Ochrona Dziedzictwa Kulturowego)
The author's reflections are based on her experience when working as the Regional Conservator of Historic Monuments in the Małopolska Region. Selected provisions of the Act on the Protection and Care of Historic Monuments will be juxtaposed with actual cases of historic buildings, in order to illustrate how the protection system works in practice. The conclusions will indicate courses of action which, often going beyond the Act, show that certain areas of activity within which we transform our surroundings are slipping away out of the constitutional - and universal - duty to uphold our heritage. Also, the conclusions will specify the things that need to be addressed in the protection system, as its emphasis has been overly shifted to antagonisms instead of cooperation.